Research on Optimal Energy Efficiency of OFDM VLC-RF Aggregation System Based on Finite Alphabet Inputs - LU Shanmei; FANG Xiao; HE Lingyan; LI Bing; MA Shuai; LI Shiyin (Kongzhi Yu Xinxi Jishu)
In the case of finite alphabet inputs, information transmission rate limit of orthogonal frequency division multiplexing (OFDM) visible light communications (VLC) and radio frequency (RF) aggregation systems is still unknown. Therefore, the unclosed expression information transmission rate and its lower bound with closed expression of OFDM VLC-RF aggregation system are derived based on mutual imformation function, and the problem of energy efficiency maximization is studied based on the two communication rates. Specifically, the energy efficiency maximization problem satisfying the spectrum efficiency (SE) threshold, total electric power and average optical power constraints is studied. At the same time, the Dinkelbach-type algorithm is used to transform the energy efficiency maximization nonconvex problem into a series of convex sub-problems, and then the interior point algorithm is used to solve it. Simulation results show that when SE threshold increases, energy efficiency first remains constant and then decreases, and energy efficiency based on the lower bound of information transmission rate can be used as a low complexity approximation of energy efficiency based on information transmission rate. The finite alphabet inputs VLC-RF aggregation system studied in this paper provides a new direction for practical communication aggregation system research.